Pengenalan Makharijul Pada Anak-Anak Di Lksa Yayasan Darul Aitam “Budi Mulia” Plosoklaten Kediri Dengan Menggunakan Metode Bil-Qolam - Qorry Aina (LP3M IAIFA Kediri, 2022)
Al-Qur'an is the holy book of Muslims. The revelation of Allah that has been compiled in the manuscripts of the Qur'an is the life guide for Muslims. Reading the Qur'an is a noble practice, each letter is rewarded with ten goodness as mentioned by the Prophet Muhammad in his words. However, it should be realized that although multiplying the Qur'an is good, if reading it is not in accordance with the science of recitation then it will only increase the sin for the reader. And to achieve a better quality of worship, the way to read the Qur'an needs to be improved. The general objective of this research is to provide learning tajwid for children at LKSA Budi Mulia Dsn. Bangunrejo Village. Pranggang district. Plosoklaten Kab. Kediri. And specifically the purpose of this program is to increase understanding of makharijul letters (where letters come out). Participatory action research is a research model that is looking for something to link the research process to the process of social change. The social change in question is how the empowerment process can realize three benchmarks, namely the existence of a joint commitment with the community, the existence of local leaders in the community and the existence of new institutions in the community that are built based on needs.